Primer design of the CO1 gene (Cytochrome Oxidase-1) for Sumatran elephant (Elephas maximus sumatranus) for rapid detection using real-time PCR method - MAQQITA TUNJUNG SARI; ARI SUSILOWATI; SETIA BETARIA ARITONANG; OKID PARAMA ASTIRIN; NITA ETIKAWATI; VIRA SAAMIA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Sari MT, Susilowati A, Aritonang SB, Astirin OP, Etikawati N, Saamia V. 2024. Primer design of the CO1 gene (Cytochrome Oxidase-1) for Sumatran elephant (Elephas maximus sumatranus) for rapid detection using real-time PCR method. Biodiversitas 25: 3840-3849. The population of Sumatran elephants is classified as endangered according to the IUCN due to conflicts between humans and elephants, resulting in many elephants being killed by humans to obtain ivory to be sold. The traded ivory is often processed into other ornaments. A rapid forensic examination with real-time PCR using the molecular approach of the CO1 gene (Cytochrome Oxidase-1) is necessary to determine the original species of the processed elephant ivory. This research aims to design and optimize a primer for identifying Sumatran elephants (Elephas maximus sumatranus). The CO1 gene primer for Sumatran elephants was designed using the Primer3Plus and IDT websites. The primers were used to amplify and identify the species of Sumatran elephants from blood, feces, and urine samples. Blood and feces samples were collected from Sumatran elephants at Taru Jurug Zoo Surakarta, while feces and urine samples were taken from Sumatran elephants at Ragunan Zoo Jakarta. DNA from blood and urine samples was extracted using the TIANamp Genomic DNA Kit, and DNA from feces samples was extracted using the TIANamp Stool DNA Kit. The purity and concentration of the obtained DNA extracts were measured. The designed primers were synthesized by Macrogen (Korea), and primer optimization was performed with a PCR gradient. The identification process of Sumatran elephant DNA extract samples was conducted by amplification using real-time PCR quantification with the standard curve method. The results of this research include the COI-270 primer with the sequences 3'-TTAGGTCAACCAGGCTCTCTTC-5' and 5'-AGGATATACGGTCCAACCAGTG-3', capable of amplifying the target 270 bp and having a single peak at the melt curve temperature of 79°C. The identification protocol with specific COI-270 primer can be used in forensic examinations to identify samples originating from Sumatran elephants.